Curriculum Adaptability, Project-Based Learning, and Students’ Critical Thinking Skills in Bandung Vocational Schools - Purwadhi; Ade Mubarok (CV. RADJA PUBLIKA, 2025)
Vocational schools are required to respond to rapid technological and industrial changes while simultaneously developing students’ higher-order thinking skills. However, curriculum flexibility does not always translate into meaningful classroom practices that strengthen critical thinking. This study examined the relationships among curriculum adaptability, Project-Based Learning, and students’ critical thinking skills and investigated the mediating role of Project-Based Learning in vocational schools in Bandung, Indonesia. A quantitative explanatory design with a cross-sectional survey was employed. Data were collected from 312 students from public and private vocational schools representing technology and engineering, information and communication technology, business and management, tourism and hospitality, and creative industries. The data were analyzed using Partial Least Squares Structural Equation Modelling with a bootstrapping procedure of 5,000 resamples. The results showed that curriculum adaptability was positively associated with students’ critical thinking skills (β = 0.247, p < 0.001) and Project-Based Learning implementation (β = 0.654, p < 0.001). Project-Based Learning was also positively associated with critical thinking skills (β = 0.518, p < 0.001). The indirect relationship between curriculum adaptability and critical thinking through Project-Based Learning was significant (β = 0.339, p < 0.001), indicating complementary partial mediation. The model explained 42.8% of the variance in Project-Based Learning and 51.3% of the variance in critical thinking skills. This study contributes to vocational education literature by demonstrating that curriculum adaptability supports critical thinking more effectively when translated into authentic, collaborative, investigative, and reflective project activities. The findings highlight the importance of teacher competence, industry-relevant project design, flexible assessment, and sustained school–industry collaboration.